2019
DOI: 10.1515/corrrev-2018-0105
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular concepts and approaches in corrosion and biofouling prevention

Abstract: Supramolecular chemistry is one of the exciting branches of chemistry where non-covalent interactions between molecules and the ensuing supramolecular structures have been studied for various applications. The present review provides a comprehensive outlook on the applications and potentials of supramolecular chemistry in corrosion and biofouling prevention. Reported works associating supramolecular chemistry with corrosion are systematically discussed under two sections: (i) surface coatings and (ii) corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 368 publications
0
8
0
Order By: Relevance
“…The results showed that in all cases the inhibitors can restrain both the anodic dissolution of carbon steel as well as the hydrogen evolution reaction, which may be attributed to the adsorption of inhibitor molecules on the active sites of steel substrate. 23 It is obvious that the combinations of SDS and KI, produce pronounced effects on the corrosion current density compared to those displayed by individual KI or SDS. This behavior suggests that SDS and KI have a synergistic effect in inhibiting the corrosion of carbon steel in HCl solution.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The results showed that in all cases the inhibitors can restrain both the anodic dissolution of carbon steel as well as the hydrogen evolution reaction, which may be attributed to the adsorption of inhibitor molecules on the active sites of steel substrate. 23 It is obvious that the combinations of SDS and KI, produce pronounced effects on the corrosion current density compared to those displayed by individual KI or SDS. This behavior suggests that SDS and KI have a synergistic effect in inhibiting the corrosion of carbon steel in HCl solution.…”
Section: Computational Detailsmentioning
confidence: 99%
“…31 Furthermore, this study demonstrated a new usage for corrosion inhibitors, which have been predominantly utilized as additives in corrosive media. 32,33 Although corrosion inhibitors based on jojoba oil were reported to have 100% anticorrosion efficiency (i.e., no corrosion) in a 60 min corrosion test 34 and corrosion inhibitors based on Henna leave extracts were known to improve corrosion resistance of acrylic resin, 35 to the best of our knowledge, no corrosion inhibitor can keep 100% anticorrosion efficiency for at least 1 month. The long-term corrosion resistance of TA/PEI LbL assembly likely originated from its ionic-bonding-based water stability and coordination-bonding-based surface adhesion.…”
Section: Introductionmentioning
confidence: 95%
“…The development of supramolecular chemistry has widened the scope for manufacturing smart containers by installing supramolecular nano valves into their pores [176]. The exterior of the Fe 3 O 4 @mSiO 2 nanocontainer incorporated supramolecular assemblies of hypiridynium c water soluble pillar (5)arenes, thus creating corrosion potential stimulus-responsive gates.…”
Section: Corros Mater Degrad 2022 3 For Peer Reviewmentioning
confidence: 99%